Effect of Rosiglitazone and Insulin Combination Therapy on Inflammation Parameters and Adipocytokine Levels in Patients with Type 1 DM - Metin Guclu; Ozen Oz Gul; Soner Cander; Oguzkaan Unal; Guven Ozkaya; Emre Sarandol; Canan Ersoy (Journal of Diabetes Research)
Aim. To investigate the efficacy of combined therapy of insulin and rosiglitazone on metabolic and inflammatory parameters, insulin sensitivity, and adipocytokine levels in patients with type 1 diabetes mellitus (type 1 DM). Material and Methods. A total of 61 adults with type 1 DM were randomly and prospectively assigned in open-label fashion to take insulin and rosiglitazone 4 mg/day (n=30) or insulin alone (n=31) for a period of 18 weeks while undergoing insulin therapy without acute metabolic complications. Results. Combination therapy did not significantly improve metabolic and inflammatory parameters, insulin sensitivity, and adiponectin levels. While leptin and resistin levels decreased in both groups (group 1: resistin 6.96 ± 3.06 to 4.99 ± 2.64, P=0.006; leptin 25.8 ± 17.6 to 20.1 ± 12.55, P=0.006; group 2: resistin 7.16 ± 2.30 to 5.57±2.48, P=0.031; leptin 16.72 ± 16.1 to 14.0 ± 13.4, P=0.007) Hgb and fibrinogen levels decreased only in group 1 (Hgb 13.72 ± 1.98 to 13.16 ± 1.98, P=0.015, and fibrinogen 4.00 ± 1.08 to 3.46 ± 0.90, P=0.002). Patients in both groups showed weight gain and the incidence of hypoglycemia was not lower. Discussion. The diverse favorable effects of TZDs were not fully experienced in patients with type 1 DM. These results are suggesting that insulin sensitizing and anti-inflammatory characteristics of TZDs were likely to be more pronounced in patients who were not totally devoid of endogenous insulin secretion.